The Difference in Translaminar Pressure Gradient and Neuroretinal Rim Area in Glaucoma and Healthy Subjects - Lina Siaudvytyte; Ingrida Januleviciene; Arminas Ragauskas; Laimonas Bartusis; Indre Meiliuniene; Brent Siesky; Alon Harris (Journal of Ophthalmology)
Purpose. To assess differences in translaminar pressure gradient (TPG) and neuroretinal rim area (NRA) in patients with normal tension glaucoma (NTG), high tension glaucoma (HTG), and healthy controls. Methods. 27 patients with NTG, HTG, and healthy controls were included in the prospective pilot study (each group consisted of 9 patients). Intraocular pressure (IOP), intracranial pressure (ICP), and confocal laser scanning tomography were assessed. TPG was calculated as the difference of IOP minus ICP. ICP was measured using noninvasive two-depth transcranial Doppler device. The level of significance P < 0.05 was considered significant. Results. NTG patients had significantly lower IOP (13.7(1.6) mmHg), NRA (0.97(0.36) mm2), comparing with HTG and healthy subjects, P < 0.05. ICP was lower in NTG (7.4(2.7) mmHg), compared with HTG (8.9(1.9) mmHg) and healthy subjects (10.5(3.0) mmHg); however, the difference between groups was not statistically significant (P>0.05). The difference between TPG for healthy (5.4(7.7) mmHg) and glaucomatous eyes (NTG 6.3(3.1) mmHg, HTG 15.7(7.7) mmHg) was statistically significant (P < 0.001). Higher TPG was correlated with decreased NRA (r = −0.83; P = 0.01) in the NTG group. Conclusion. Translaminar pressure gradient was higher in glaucoma patients. Reduction of NRA was related to higher TPG in NTG patients. Further prospective studies are warranted to investigate the involvement of TPG in glaucoma management.